Fresh tomato: promissing export product for Serbia? - Vuković, Andrea; Ubiparip, Dragana; Radovanović, Maja; Jaćimović, Sonja (Industrija, 2015)
Production of fresh vegetable is in Serbia often emphasized as a sector with promising export potential. However, available analysis and recommendations are mainly of general character without comprehensive data enabling applicable recommendations for improved utilization of existing potentials. In order to eneble thorough insight into the sector of production of fresh tomato and its export potentials, analysis of production and international trade trends in Serbia and potential target markets was conducted based on statistical data. Additionally, tomato supply chain structure in Seriba was reviewad based on a series of interviews. Obtained results pointed out at the markets of Central and Eastern Europe as potential target markets for fresh tomato from Serbia, but indicated a number of improvement that are prerequisite for competitive utilization of fresh tomato production potentials in Serbia. Improvements are needed in production practices leading to improvement of quantitiy, quality, safety and uniformity of produced tomato, but above all in organization of supply chain.
Keywords: Supply chain; Competitiveness; International trade; Export; Tomato